Linear models for the prediction of animal breeding [ - Mrode, Raphael A.; Thompson, R. (CABI, 2005)
Best Linear Unbiased Prediction (BLUP) has become the most widely accepted method for genetic evaluation of domestic livestock. Since its introduction, the method has evolved and despite this there is no simple text on the application of linear models t the predictions of breeding values. This book has been written with a good balance of theory and application to fill this gap. Equations for partitioning breeding values into contributions from various sources of information are derived under the various models. Recent developments in the analysis of longitudinal data with random. regression models and the inclusion of genetic marker information in the evaluation of animals have been incorporated. Threshold models have been introduced in addition to the basic concepts and methods for variance compenent estimation including the use of the Gibbs sampler. Overall, the book has been thoroughly updated since the first edition was published in 1996. It will appeal to advanced students in animal breeding and genetics.